2022
DOI: 10.1021/acs.jpclett.2c02710
|View full text |Cite
|
Sign up to set email alerts
|

Trap-Filling Magnetoconductance as an Initialization and Readout Mechanism of Triplet Exciton Spins

Abstract: Photoexcited triplet states are promising candidates for hybrid qubit systems, as they can be used as a controlling gate for nuclear spins. But microwave readout schemes do not generally offer the sensitivity needed to approach the single-molecule limit or the scope to integrate such systems into devices. Here, we demonstrate the possibility of electrical readout of triplet spins at room temperature through a specific mechanism of magnetoconductance (MC) in polycrystalline pentacene. We show that hole-only pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…The model we use, referred to here as the exciton-carrier annihilation (ECA) model, is described in Equation ( 1) and ( 2 been shown to describe the kinetics of other common organic semiconductors. [34][35][36][37][38][39] d…”
Section: Exciton-carrier Annihilation Modelmentioning
confidence: 99%
“…The model we use, referred to here as the exciton-carrier annihilation (ECA) model, is described in Equation ( 1) and ( 2 been shown to describe the kinetics of other common organic semiconductors. [34][35][36][37][38][39] d…”
Section: Exciton-carrier Annihilation Modelmentioning
confidence: 99%
“…Both of these possible outcomes (quenching and scattering) might influence current in their own way. Our work has shown that such behavior dominates the magnetoconductance behavior of bulk pentacene devices, making it a potentially useful mechanism for the readout and control of triplet excitons …”
Section: Population-detected Magnetic Resonancementioning
confidence: 94%
“…The key result is shown in Figure c, giving the magnetoconductance curves in the light (red) and dark (black) regions, which were fit using our quantum kinetic model. The quartet character of the triplet–doublet encounter complex is calculated via the stochastic Liouville equation (SLE), and the magnetoconductance is modeled by solving a system of kinetic equations at steady-state with the SLE populations as an input parameter . We invoke a trap filling mechanism to explain this counterintuitive increase in conductance with the magnetic field, illustrated in Figure a,b.…”
Section: Population-detected Magnetic Resonancementioning
confidence: 99%
See 2 more Smart Citations